Pengaruh Strategi Example Non Example dengan Media Benda Konkret Terhadap Hasil Belajar IPA Pada Kelas V SD Negeri 2 Tegalgede Tahun Pelajaran 2015/2016 - Setyo Hutomo, Catur (2016)
This research aims to know is there any influence and how big the influence strategy example non example with media objects, concrete results towards learning IPA on class V SD Negeri 2 Tegalgede. This type of research is the research experiments. Data analysis using simple regression test (test F), hypothesis test (test t) and a test of determination (r2). With the results obtained from the research of init, as follows: t-test analysis results between variable strategy example non example with concrete objects and variable media the results of the study on the experimental class retrieved thitung ttabel 2.048 and 3.866. The results of calculation show that thitung > ttabel 2.048 3.866. This shows that the hypothesis that States "there is an influence on the implementation of the strategy for example non example concrete objects with media" can be accepted. On the test F (keberartian regression test) to test whether there is a linear relationship between the variables (X) and (Y), acquired F count = and Ftabel = 4.17. F calculate 14.974 > Ftabel 4.17. This shows that there is a linear relationship between strategy example non example with media objects, concrete (X) with the results of learning IPA (Y). On test strategies known example of non r2 example concrete objects with media influence of 35% for the enhancement of student learning outcomes. It can be concluded that the application of the strategy example non example with media objects, concrete results towards learning the IPA grade V has increased.